UMP honours special children - Nor Salwana, Mohammad Idris (2020)
Pekan, 22 August 2020 - To enliven the Independence Month Celebration at Universiti Malaysia Pahang (UMP), 63 special children were celebrated and received assistance in the UMP Program Prihatin organised by the UMP Foundation in collaboration with the Office of the Vice-Chancellor (PNC).